Recent progress on harm, pathogen classification, control and pathogenic molecular mechanism of anthracnose of oil-tea - Chen, Xinggang; Chen, Xingzhou; Tan, Qian; Mo, Xiuli; Liu, Junang; Zhou, Guoying (Frontiers in Microbiology, 2022)
Oil tea (Camellia oleifera), mainly used to produce high-quality edible oil, is an important cash crop in China. Anthracnose of oil tea is a considerable factor that limits the yield of tea oil. After years of efforts, great progress has been made in the research of oil tea anthracnose. The authors summarized the research status of the harm, pathogen types, control and pathogenic molecular mechanism of oil tea anthracnose, in order to provide theoretical support and new technical means for the green prevention and control of oil tea anthracnose.